Streptozotocin-induced type 1 and 2 diabetes in rodents: a model for studying diabetic cardiac autonomic neuropathy - Mathias Akinlade, Olawale; Victor Owoyele, Bamidele; Olufemi Soladoye, Ayodele (African health sciences, 2021)
Background: Several animal models are continually being developed to study diabetic complication. Several conflicting regimen for diabetes induction exist in the literature with varying dose strength and regimen for different study interest in diabetes. This study aims to show the effect of high dose streptozotocin (STZ) on the one hand compared with multiple low doses after high fat diet induction on diabetic cardiac autonomic neuropathy (DCAN). Methodology: Eighty-four Wistar rats were used to demonstrate DCAN induction using 2 approaches one for T1DM (STZ 50mg/kg) and the other for T2DM (HFD for 8 weeks with STZ 25mg/Kg daily for five days). DCAN features were assessed using invasive biomarkers, histology patterns and cardiac nerve densities. Results: Diabetes induction rate was 76% and 89% in T1DM and T2DM model respectively. T1DM group had significant weight loss, reduced c-peptide, and insulin level post induction. The T2DM additionally showed significantly higher total cholesterol and Homeostatic model assessment (HOMA) compared with control. Serum levels of catecholamine, choactase, nerve growth factor and cardiac nerve density confirms development of DCAN. Conclusion: High single dose of STZ and HFD with multiple low doses of STZ may be recommended for DCAN study in T1DM and T2DM rat model respectively. Keywords: Diabetic cardiac autonomic neuropathy; Diabetes mellitus; Heart rate variability; Streptozotocin.